The Effectiveness of the Implementation of the Quick Response Code Indonesia Standard (QRIS) Payment System for MSMEs - Nisa, Sakinatun; Adinugraha, Hendri Hermawan (Journal of Economics, Management, Accounting and Computer Applications, 2024)
The rapid advancement of technology has brought significant changes in society, particularly in the economic sector. The latest technological developments, especially in financial technology, have facilitated Indonesians in their daily activities, access to information, and business development. The rise of digital economy through innovations in financial technology has led to the emergence of cashless payment systems, such as QR code-based payment systems. Despite the benefits of these systems, challenges such as inadequate internet infrastructure and lack of public participation hinder their effectiveness, especially in rural areas like Rowoyoso village in Pekalongan Regency. This study aims to explore the effectiveness of implementing the QRIS payment system for Micro, Small, and Medium Enterprises in Rowoyoso Village, Pekalongan Regency. The qualitative research approach involves data collection through interviews with MSMEs owners and observations at the research site. Findings indicate that while QRIS offers convenience and transparency in financial transactions, challenges such as poor internet connectivity and low community participation pose barriers to its successful implementation. The research contributes to understanding the impact of digital payment systems on MSMEs and highlights the importance of addressing infrastructure and community engagement issues for the effective adoption of QRIS. The findings suggest that QRIS can enhance business operations, streamline financial management, and improve security compared to traditional cash transactions. By evaluating the effectiveness of the QRIS payment system, this study provides insights for policymakers, financial institutions, and MSMEs owners to enhance the digital payment ecosystem in rural areas like Rowoyoso village.